Chromatographic Studies on Triphala - A.S. BAHULIKAR, MS.; R.V. KASHALKAR, MS.; PUNDLIK, M.D. (Asian Journal of Chemistry, 2010)
Chromatographic studies on Triphala, a well known ayurvedic formulation, prepared from three constituents, viz., Haritaki, Beheda and Amalaki, have been carried out with a view to standardize the formulation. Thin layer chromatographic studies were carried out using precoated silica gel fluorescent plates on the aqueous extracts and ethyl acetate extracts of the three constituents and also Triphala The choice of the solvent system toluene-ethyl acetate-formic acid is discussed and its utility is demonstrated for complete resolution of gallic acid from other components. Gallic acid therefore can be used as a marker compound for standardizing Triphala